Biological and psychological influences of cross-sex hormone in transgender - Ling, SL; Hatta Sidi; Azlin B (Pusat Perubatan Universiti Kebangsaan Malaysia, 2019)
Transgender is a complex state of bio-psycho-social dimension of human sexuality. It encompasses cognitive-emotional-behavior component that makes the person unique in his or her sexual expression. Transgender tend to use cross-sex hormone in order to eradicate their secondary sexual characteristics and to facilitate the shift to their experienced gender. The common masculinising sex hormone use, i.e. Female to Male Treatment Options (FMTO) is testosterone and for feminising hormone i.e. Male to Female Treatment Options (MFTO) is a combination of estrogen with anti-androgen, respectively. Cross-sex hormone, i.e. FMTO, or MFTO has biological and psychological influences on the transgender individuals. Nevertheless, cross-sex hormone may also pose a range of side effect profiles, varies from the biological to psychosocial impact. The psychological impact can be paramount until it causes severe mental-health problems and even suicide. Numerous ranges of bio-psycho-social influence of cross-sex hormone were highlighted in this review as fundamental core knowledge in the art to know practice when dealing with the treatment options. In psychiatry, the change in the biological appearance may have great influence in the transgender individual, especially in the context of psychosocial and cultural perspective.